1997
DOI: 10.1046/j.1471-4159.1997.68010233.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Administration of the Dopaminergic Agonists l‐DOPA, Amphetamine, and Cocaine Increases Dopamine Activity in the Neostriatum: A Microdialysis Study in the Rat

Abstract: The effectiveness of intranasal drug administration to stimulate central neuronal systems is well known from drug addiction and has also been considered as an alternative pharmacokinetic approach to treat brain disorders such as Parkinson's disease. In the present study, the possible neurochemical effects of intranasal administration of the psychostimulants cocaine and amphetamine and of the antiparkinsonian drug l‐DOPA were analyzed. By using in vivo microdialysis in the urethane‐anesthetized rat, it was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…As postulated [81] , behavioral and neurochemical effects of labelled DA applied either by intra-nasal or intravenous route should be compared to validate the uptake and distribution of labelled DA in the brain in future studies. Nevertheless, the rapid behavioral effects in the present study along with quick neurochemical effects in our previous ones [10][11][12] , strongly suggest a fast transport mechanism into the brain. Thus, the intra-nasal application procedure may represent a valuable alternative for targeting the brain with exogenous DA, resulting in rapid neurochemical and behavioral effects.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…As postulated [81] , behavioral and neurochemical effects of labelled DA applied either by intra-nasal or intravenous route should be compared to validate the uptake and distribution of labelled DA in the brain in future studies. Nevertheless, the rapid behavioral effects in the present study along with quick neurochemical effects in our previous ones [10][11][12] , strongly suggest a fast transport mechanism into the brain. Thus, the intra-nasal application procedure may represent a valuable alternative for targeting the brain with exogenous DA, resulting in rapid neurochemical and behavioral effects.…”
Section: Discussionsupporting
confidence: 42%
“…Previously, we demonstrated that L -DOPA readily enters the brain upon intra-nasal application, leading to increases in extracellular levels of DA in neostriatal regions [10,11] . Additionally, recently, we found evidence that DA, administered intra-nasally in the rat, can also enter the brain, leading to an immediate pronounced increase in extracellular DA levels in striatal subregions [12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ventral striatum, dorsal striatum, medial prefrontal cortex, hippocampus, entorhinal cortex, and occipital cortex were dissected, homogenized, centrifuged, filtered, and stored at −80°C until analysis for dopamine and serotonin content (De Souza Silva et al 1997). Samples, containing 400 pg deoxyepinephrine as an internal standard, were analyzed by high-performance liquid chromatography with electrochemical detection.…”
Section: Post Mortem Neurochemistrymentioning
confidence: 99%
“…Instead of the oral and intravenous route, the intranasal drug administration is receiving great consideration as a promising pharmacokinetic approach for the PD treatment. To this regard, de Souza Silva and colleagues, for the first time, showed by in vivo microdialysis that intranasal administration of dopaminergic drugs such as the psychostimulants cocaine and amphetamine or the antiparkinsonian drug L-Dopa can increase extracellular DA levels in the striatum [9,10]. These interesting results have encouraged further to pursuit of this approach.…”
Section: Introductionmentioning
confidence: 99%